The Effectiveness of CPNS Basic Training in Lecturer Human Resource Development at the Ministry of Religious Affairs - Edi Sugianto; Lina Herlina; Abdul Hamid Arribathi (Universitas Muhammadiyah Tangerang, 2026)
The Basic Training Programme for Civil Service Candidates (Latsar CPNS) is a government initiative aimed at improving the competence, integrity, and professionalism of civil servants, including lecturers at the Ministry of Religious Affairs. This study analyses the effectiveness of the 2025 Latsar CPNS programme in developing human resources for lecturers, based on the participants' perspectives. Using a qualitative and descriptive-analytical approach, data was collected through written interviews conducted via an online questionnaire (Google Form) and by analysing relevant documents. The focus of this study was on CPNS lecturers from the Ministry of Religious Affairs who participated in the 2025 Basic Training Programme. The data analysis process followed the stages of reduction, presentation, and conclusion drawing. The results of the study indicate that the 2025 Basic Training Programme is generally considered effective in strengthening the basic competencies of lecturers. This programme has succeeded in supporting the internalisation of the basic values of civil servantsâ€”service orientation, accountability, competence, harmony, loyalty, adaptation, and collaborationâ€”as well as increasing lecturers' understanding of their roles as civil servants and encouraging professional behaviour and academic ethics. However, this study found challenges such as the limited contextuality of the training material in relation to the lecturers' threefold duties and the increased administrative burden during the implementation of the programme. Therefore, this study recommends the development of a more adaptive and profession-specific Basic Training model to better support human resource development for lecturers at the Ministry of Religious Affairs.Â